THE HIDDEN COSTS OF INTERNATIONAL TRADE - Amala, Istiqomah Ahsanu (Politeknik Bisnis Indonesia, 2024)
The rapid growth of international trade in recent decades has become essential in increasing economic prosperity and strengthening relations between countries worldwide. However, this growth also raises various negative impacts that must be well understood. This study aims to identify and analyze these negative impacts and mitigation strategies that can be implemented to reduce or avoid these impacts. This study uses the Systematic Literature Review (SLR) method. A systematic Literature Review (SLR) is a method used to identify, assess, and compile all literature relevant to a research topic systematically and transparently to find strategies to help overcome the negative impacts of international trade. The study results show that international trade has a significant negative impact. These negative impacts include unhealthy competition, job losses, environmental impacts, social injustice, a decline in primate and other species populations, economic inequality, cultural damage, and development inequality. Efforts are needed to overcome these negative impacts so that international trade can sustainably benefit all parties.